Supreme effort goes unrewarded: President's Cup: No trophy for league winners despite arduous competition - Singh, Devinder (New Straits Times, 2013)
AT the conclusion of the league stage of the President's Cup, the teams will have toiled for 34 matches since Jan 31. but there will be no recognition in terms of a trophy or prize money for whoever that come out on top. The President's Cup will only be awarded to the winners of a knockout stage involving the top eight teams from the league.